2011
DOI: 10.4103/0973-8258.85183
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacognostic screening and phytochemical evaluation of Acacia leucophloea root

Abstract: Acacia leucophloea (Mimosoideae) is native to Southeastern Asia. This tree species has been of interest to researchers because it is a medicinal plant employed in the Indian indigenous system of medicine. Pharmacognostic standardization, physico-chemical evaluation of the roots of Acacia leucophloea was carried out to determine its macro-and micro-scopical characters and also some of its quantitative standards. Microscopical studies were done by using trinocular microscope. Total ash, water-soluble ash, acidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…12 The bark of the thorny tropical and subtropical tree A. leucophloea is an important component in the Indian traditional medicine system, where it is used for various treatments, including wound care. 13 The extracts from this bark are found to contain various bioactive components 14 that not only scientifically validate their use in traditional medicine, but also the study of their participation in self-assembling and capping metal NPs. 2 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 The bark of the thorny tropical and subtropical tree A. leucophloea is an important component in the Indian traditional medicine system, where it is used for various treatments, including wound care. 13 The extracts from this bark are found to contain various bioactive components 14 that not only scientifically validate their use in traditional medicine, but also the study of their participation in self-assembling and capping metal NPs. 2 …”
Section: Discussionmentioning
confidence: 99%
“…The gum and bark decoction is used as an anticontraceptive and menstrual complaint regulator. 13 The aqueous extract of the tree contains phytochemicals such as amino acids, alkaloids, carbohydrates, flavonoids, glycosides, steroids, and tannins, whereas the ethanolic extract is found to contain amino acids, alkaloids, glycosides, flavonoids, tannins, and steroids. 14 The tree extracts have also been found to contain phytoconstituents such as n-hexacosanol, b-amyrin, b-sitosterol, and tannin as major compounds.…”
mentioning
confidence: 99%
“…The dried powders of root, stem, leaf and seeds were observed under high-power (10X, 40X) microscope (Metzer) with stain (safranin and fast green) and without stain, mounted in glycerin, and various diagnostic characters such as stoma, trichomes, lignified fibers, xylem, sclereids are studied [21,29,40].…”
Section: Powder Microscopymentioning
confidence: 99%
“…(2010), Jain et al (2011), Paul et al (2011 and Sudhakar et al (2012) who reported similar features of roots and fruits of various medicinal plants. According to the Thai Herbal Pharmacopeia (THP), essential instruments for plant identification include macroscopic approaches.…”
Section: Macroscopic Evaluationmentioning
confidence: 90%